2020
DOI: 10.1126/sciadv.aaz5041
|View full text |Cite
|
Sign up to set email alerts
|

CDK13 cooperates with CDK12 to control global RNA polymerase II processivity

Abstract: The RNA polymerase II (POLII)–driven transcription cycle is tightly regulated at distinct checkpoints by cyclin-dependent kinases (CDKs) and their cognate cyclins. The molecular events underpinning transcriptional elongation, processivity, and the CDK-cyclin pair(s) involved remain poorly understood. Using CRISPR-Cas9 homology-directed repair, we generated analog-sensitive kinase variants of CDK12 and CDK13 to probe their individual and shared biological and molecular roles. Single inhibition of CDK12 or CDK13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 45 publications
7
100
1
Order By: Relevance
“…1C,D), we nevertheless probed the RNA-seq data for evidence that CDK12 inhibition was occurring. Others have shown that CDK12 inhibition results in premature, intronic polyadenylation (iPA) (Dubbury et al 2018;Krajewska et al 2019;Fan et al 2020), which causes reduced exon read counts toward gene 3 ′ ends. A DEXSeq analysis (Anders et al 2012) showed no evidence for iPA genome-wide in cells treated with SY-351 (Supplemental Fig.…”
Section: Inhibition Of Cdk7 Causes Diverse and Widespread Splicing Changesmentioning
confidence: 99%
“…1C,D), we nevertheless probed the RNA-seq data for evidence that CDK12 inhibition was occurring. Others have shown that CDK12 inhibition results in premature, intronic polyadenylation (iPA) (Dubbury et al 2018;Krajewska et al 2019;Fan et al 2020), which causes reduced exon read counts toward gene 3 ′ ends. A DEXSeq analysis (Anders et al 2012) showed no evidence for iPA genome-wide in cells treated with SY-351 (Supplemental Fig.…”
Section: Inhibition Of Cdk7 Causes Diverse and Widespread Splicing Changesmentioning
confidence: 99%
“…CDKs regulating gene expression apart from cell cycle control constitute additional therapeutic targets. Specifically, the CDKs 7/8/9/12/13 are involved in RNA polymerase II transcription regulation [50][51][52]. Though the complexity exceeds the scope of this review, we included some information gathered from HNSCC and GBM studies inhibiting these CDK's.…”
Section: Cdk7/8/9/12/13 Inhibitorsmentioning
confidence: 99%
“…The studies suggested that the identified substrates of CDKL5 kinase might be important biomarkers in the diagnosis and treatment of CDKL5 disorders. Additionally, the CDK12 and CDK13 have been identified as fundamental regulators of the global PolII processivity and transcription elongation [ 96 , 97 , 98 , 99 , 100 ].…”
Section: Analog-sensitive Kinase Technologymentioning
confidence: 99%